2021
DOI: 10.3389/fcvm.2021.751052
|View full text |Cite
|
Sign up to set email alerts
|

U-Shaped Association of the Heart Rate Variability Triangular Index and Mortality in Hemodialysis Patients With Atrial Fibrillation

Abstract: Background: Atrial fibrillation (AF) is common in hemodialysis patients and contributes to increased mortality. We aimed to examine heart rate variability triangular index (HRVI) in hemodialysis patients with AF as it has recently been reported to predict mortality in AF patients without kidney disease.Methods: A total of 88 patients on hemodialysis with a medical history of AF or newly diagnosed AF underwent 24-h electrocardiography recordings. The primary endpoint of cardiovascular mortality was recorded dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Based on retrospective analyses of various risk stratification techniques, SCD was found to be associated with depressed HRV in 24-h recordings and can be predicted by some HRV metrics with relatively high accuracy [ 24 , 25 ]. For instance, Braunisch et al [ 26 ] observed a U-shaped association between HRVTI and mortality in hemodialysis atrial fibrillation patients. This result might contribute to risk stratification independent of known risk scores in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on retrospective analyses of various risk stratification techniques, SCD was found to be associated with depressed HRV in 24-h recordings and can be predicted by some HRV metrics with relatively high accuracy [ 24 , 25 ]. For instance, Braunisch et al [ 26 ] observed a U-shaped association between HRVTI and mortality in hemodialysis atrial fibrillation patients. This result might contribute to risk stratification independent of known risk scores in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Huikuri et al proved that an extremely lower HRV metric indicated true autonomic dysfunction, but a higher value of the metric might not always reflected more healthy autonomic function, it might be an indicator of an unhealthy and highly irregular pattern, such as erratic rhythms [ 9 ]. Shaffer et al also demonstrated that pathological conditions and cardiac conduction abnormalities might increase HRV metrics, and the increased HRV metrics were strongly associated with the increased risk of mortality [ 26 ]. Our results also confirmed that the methodologies used have a great impact on HRV analysis and can be used to explain the discrepancies of the clinical studies.…”
Section: Discussionmentioning
confidence: 99%